GENDER DISCRIMINATION - Singh, Chandan Kumar; Mamta Rani (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Over the course of the last several years, there has been a significant amount of attention paid to the grave issue of women in India misusing the judicial system. The fact that women in India are often subjected to discrimination and do not have equal rights and opportunities contributes to the existence of gender bias in many aspects of Indian society. However, the fact that women often take advantage of the judicial system just helps to exacerbate the gender bias that already exists. Throughout the history of the legal system, there have been several instances of women attaining their objectives, sometimes at the expense of men. This behaviour is not only inappropriate from a moral standpoint, but it also goes against the Constitution. In the Indian Constitution, there is no section that specifically addresses the issue of gender equality. Over the course of its history, the Constitution has been subjected to several amendments in order to ensure that women are afforded equal legal protection. It is a fundamental human right to ensure that women are protected from any kind of discrimination, regardless of circumstances. Despite this, prejudice against women continues to exist in many aspects of society, such as the marriage market, the job, and educational institutions. In India, the most prevalent instances of women misusing the judicial system are those that include domestic violence and offences involving dowries. According to Indian law, crimes that include dowries are considered to be of a criminal character and entail criminal consequences. Instead, women often create charges of dowry harassment against their husbands or in-laws in order to achieve what they want in a divorce or property dispute. This is done in order to get what they want. Because of this misuse, men are deprived of the rights that are rightfully theirs, in addition to eroding the value of the law. To add insult to injury, when confronted with charges of domestic violence, law enforcement officers often do nothing, so allowing the perpetrators of the abuse to take the blame. This violates not just the rights of the victims but also sends the message that violence against women is acceptable. One of the most significant issues that has to be addressed is the fact that women in India are misusing the judicial system. In accordance with the provisions of the Indian Constitution, which guarantees gender equality, it is the responsibility of the government to ensure that women are afforded equal rights and opportunities. It is imperative that we take precautions to prevent women from exploiting the legal system and to ensure that they are afforded enough protection against discrimination on the basis of their gender. Furthermore, individuals who are culpable for this crime should be subjected to the full force of the law, and victims of gender-based violence should get proper assistance and protection while they are victims.